Members and Nonmembers: Determinants of Dues-Paying Membership in a Bargaining Unit - McClendon, John A. (Relations industrielles / Industrial Relations, 2000)
This study builds on the union organizing and free-rider literature by examining determinants of dues-paying membership in the Temple Association of University Professionals. The TAUP, an American Federation of Teachers affiliate, is the collective bargaining representative for 992 members of the Temple University faculty, 52% of whom are dues-paying members. Results indicate that attitudes about unions in general, the cost of union dues, the perception of alternative faculty governance effectiveness, and the beliefs about the appropriateness of unionization for professional employees were related to joining behavior. In contrast, job attitudes about the employer, perceived bargaining unit effectiveness, and political ideology were not significant predictors of membership status.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Colleges & universities; Educators; Labor Unions; Memberships; Professions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Union membership